FANATICISM: AN ANALYSIS ON BTS’ “ARMY” FAN BEHAVIOR ON TWITTER - Lambok Hermanto Sihombing; Syafa Azzahra Putri Andini (Jurnal Mutakallimin : Jurnal Ilmu Komunikasi, 2022)
Fandom is the main support system for its idol. Every fandom has its own method to express their support and love toward their idol – they also motivate themselves to help their idol in achieving the most success in their career. Hence, every fandom is willing to thrive and support their idol in every possible way. Nonetheless, some fandoms may express their support in an aggressive way due to their extreme enthusiasm and obsession with their idol. ARMY is one of the fanatic K-Pop fandoms that is known to express their support in extreme behavior in which it makes them gain the label ‘toxic fandom’ by the internet users.